Gender differences in vitiligo: psychological symptoms and quality of life assessment description - Samela, Tonia; Malorni, Walter; Matarrese, Paola; Mattia, Gianfranco; Alfani, Stefania; Abeni, Damiano (Frontiers in Psychology, 2023)
Objective: Assuming the differences existing in the manifestation of psychological suffering among genders, the purpose of this review is to summarize the current knowledge on gender differences in vitiligo quality of life and psychological assessment.We searched in PubMed, Scopus, and Web of Science databases for original articles in English language. Results were screened according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA checklist).The study yielded 107 results; 12 articles have been evaluated as eligible. Each eligible study has been screened and analyzed. The study's qualitative evaluation revealed that 8 papers were classifiable as satisfactory, 4 were classifiable as unsatisfactory. The agreement between the coders was high (% agreement = 84.6%; Cohen's kappa = 0.79). All considered researches (100%) were cross-sectional studies, based on self-report questionnaires. From our analysis, women with vitiligo had a higher risk to experience lower quality of life, and worse mental health in a wide range of psychopathology symptoms than men. A wide heterogeneity of tools is used to investigate the quality of life and psychological symptoms among these patients.Unfortunately, there are few explanatory models proposed in the literature to rationalize these findings. It will be important to investigate in further researches the specific influence of known risk factors for psychopathology) in this population to better explore these phenomena.